Cross-generational mechanisms of maternal gut microbiota in modulating offspring autism spectrum disorder risk: from the gut-brain axis to translational challenges in precision interventions - Zhang, Dashuang; Zhou, Min; Qiu, Yudan; Xu, Hong; Liu, Hanmin; Liu, Yang; Xie, Liang (Frontiers in Aging Neuroscience, 2025)
Autism Spectrum Disorder (ASD) manifests as a group of neurodevelopmental disorders with high clinical and genetic heterogeneity, characterized by core features including social communication deficits, repetitive behaviors, and restricted interests. Current research primarily focuses on genetic variations, immune dysregulation, synaptic dysfunction, and gene–environment interactions. Nowadays, accumulating evidence indicates that maternal gut microbiota dysbiosis, induced by high-fat diets, antibiotic overuse, and urbanization, significantly correlates with abnormal fetal neurodevelopment and increased ASD risk. This review systematically delineates three transplacental mechanisms whereby maternal dysbiosis regulates fetal neurodevelopment: Metabolite-mediated pathways, Immune pathway activation, and Epigenetic reprogramming. Meanwhile, the key translational challenges are highlighted. At last, metagenomics-metabolomics-fetal neuroimaging, Development of microbiota metabolite-treated brain organoids, and Artificial Intelligence-driven (AI-driven) probiotic screening were proposed as research directions in future.